2011
DOI: 10.1007/978-3-642-22012-8_36
|View full text |Cite
|
Sign up to set email alerts
|

Liveness-Preserving Atomicity Abstraction

Abstract: Abstract. Modern concurrent algorithms are usually encapsulated in libraries, and complex algorithms are often constructed using libraries of simpler ones. We present the first theorem that allows harnessing this structure to give compositional liveness proofs to concurrent algorithms and their clients. We show that, while proving a liveness property of a client using a concurrent library, we can soundly replace the library by another one related to the original library by a generalisation of a well-known noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
(30 reference statements)
1
44
0
Order By: Relevance
“…All the definitions of linearizability proposed for various settings so far [11,8,10,9] have assumed a sequentially consistent memory model. This paper is the first to define a notion of linearizability on a weak memory model and show that it validates the Abstraction Theorem (Theorem 4).…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…All the definitions of linearizability proposed for various settings so far [11,8,10,9] have assumed a sequentially consistent memory model. This paper is the first to define a notion of linearizability on a weak memory model and show that it validates the Abstraction Theorem (Theorem 4).…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…We hope to lift this restriction by combining our results with a recent generalisation of classical linearizability allowing transfers of memory ownership [9]. Similarly, a previous generalisation of linearizability to handle liveness properties [8] could be used to strengthen specifications of the kind shown in Figure 1a to guarantee properties such as lock-freedom.…”
Section: Discussionmentioning
confidence: 88%
“…Recent work has formalised the intuition that linearizability corresponds to observational abstraction [6] and has extended it to handle liveness [8], resource-transferring programs [9] and the x86 memory model [4]. The latter work is the closest to this paper; in particular, we borrow the decompose-compose approach in the proof of the Abstraction Theorem ( §6.3) from it.…”
Section: Related Workmentioning
confidence: 99%
“…Gotsman and Yang [6] propose a new linearizability definition that preserves lock-freedom, and suggest a connection between lock-freedom and a terminationsensitive contextual refinement. We do not redefine linearizability here.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…To obtain equivalence to linearizability, the observable behaviors include I/O events but not divergence (i.e., non-termination). Recently, Gotsman and Yang [6] showed that a client program that diverges using a linearizable and lock-free object must also diverge when using the abstract operations instead. Their work reveals a connection between lock-freedom and a form of contextual refinement which preserves termination as well as safety properties.…”
Section: Introductionmentioning
confidence: 99%